Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/jcu.23495
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced myometrial vascularity and AVM: A review on diagnosis and management

Abstract: Uterine Arteriovenous malformations (AVM) are vascular disorders characterized by complex high‐flow tangles of abnormal vessels connecting arteries and veins with bypassing capillaries. Recently, the terminology applied to describe uterine AVMs has been modified. Most AVMs are acquired. The term enhanced myometrial vascularity (EMV) is used to describe any condition in which any uterine pathology may lead to increased myometrial vascularity regardless of the absence or presence of residual tissue of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Uterine AVM are rare, and the true prevalence is unknown, 5,8 but estimates have reported 0.63% following abortion or parturition. 3 Acquired EVM/AVM are fistula-like structures formed as a result of the incorporation of necrotic chorionic villi into the venous sinuses of scar tissue 3 and are associated with RPOC and the improper healing of uterine trauma and instrumentation, such as Cesarean section, dilatation, and curettage, trophoblastic disease, neoplasms, or surgery. 9,10 An evaluation of selected case reports/series with detailed symptoms and diagnostic imaging details (Supplemental Table 1) revealed that abnormal vaginal bleeding is the most common symptom of AVM, ranging in severity from frequent spotting to catastrophic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uterine AVM are rare, and the true prevalence is unknown, 5,8 but estimates have reported 0.63% following abortion or parturition. 3 Acquired EVM/AVM are fistula-like structures formed as a result of the incorporation of necrotic chorionic villi into the venous sinuses of scar tissue 3 and are associated with RPOC and the improper healing of uterine trauma and instrumentation, such as Cesarean section, dilatation, and curettage, trophoblastic disease, neoplasms, or surgery. 9,10 An evaluation of selected case reports/series with detailed symptoms and diagnostic imaging details (Supplemental Table 1) revealed that abnormal vaginal bleeding is the most common symptom of AVM, ranging in severity from frequent spotting to catastrophic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine arteriovenous malformations (AVM) involve an abnormal connection between branches of the uterine artery and the venous plexus within the myometrium, bypassing capillaries, and are characterized by complex high-flow tangles of abnormal vessels. [1][2][3] Arteriovenous malformation can develop as a pre-existing pathologic uterine process or be acquired as a result of trauma, surgical intervention, or Cesarean section. 4 Enhanced myometrial vascularity/uterine arteriovenous malformations (EVM/AVM; acquired AVM) are rare causes of vaginal bleeding that can result in life-threatening hemorrhage if left untreated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An arteriovenous malformation (AVM) is an abnormal and non-functional connection between arteries and veins [1,2]. A uterine AVM is an abnormal connection between arteries and veins that is specifically located in the uterus and involves the uterine arteries [3,4]. These malformations often present with significant hemorrhage, which is usually described as sporadic, although some cases report incidental findings in an asymptomatic patient [1,5].…”
Section: Introductionmentioning
confidence: 99%